Investigação experimental e modelagem do efeito da temperatura sobre a produção de lipases por Aspergillus niger C em cultivo em estado sólido - Andrade, João Victor de Oliveira (Universidade Federal de São Carlos, 2022)
Since the technological development of a clean and renewable energy matrix became strategic for Brazil, the concept of biorefinery has emerged as an industry focused on the production of biofuels, with emphasis on biodiesel. Particularly, for biochemical synthesis of biodiesel, lipolytic enzymes are required, which in turn can be produced in the plant itself by solid state fermentation (FES), a bioprocess that uses biorefinery by-products as substrates, allowing a certain self-sufficiency of the unit. However, data on the metabolism of lipase-producing fungi in FES are still scarce, making simulation and scale-up studies of bioreactors difficult. on the production of enzymes with lipolytic activity by the fungus Aspergillus niger C cultivated in agro-industrial residues. Data on protein concentration and lipase activity obtained from flask-scale cultures at different temperatures were collected, as well as data from literature on lipase enzymatic activities obtained from the cultivation of the same fungus, using the same substrate. These data were used to determine the kinetic constants of lipase production, based on zero-order, first-order and logistic models, at different temperatures. With the kinetic constants, the temperature effect was modeled by the Arrhenius equation. A modeling of the thermostability of the enzymes produced was also carried out, using data from the literature. With this, the aim was to raise reliable kinetic parameters for future studies of heat transfer simulation in the bioprocess of production of lipase for biodiesel in FES bioreactors.
Experimental research and modeling of the effect of temperature on the production of lipases by Aspergillus niger C in solid-state culture
Keywords: Fermentação em estado sólido; Biodiesel; Biocombustíveis; ENGENHARIAS::ENGENHARIA QUIMICA